Ultrasound‐guided peripheral deep vein cannulation to perform automated red cell exchange—A pilot study in a single centre. Issue 6 (26th November 2015) - Putensen, Daniel; Pilcher, Linda; Collier, Dawn; McInerney, Karen
Abstract : Background: Securing adequate vascular access is essential for a successful apheresis procedure. In most, peripheral access is preferred but it is not always technically possible. Ultrasound‐Guided Peripheral Vascular Access (USG‐PIVA) is a well‐documented technique in the setting of Emergency departments. However, limited data exists reporting its use in the context of automated red cell exchanges (a‐RCEx). Purpose: To assess the effectiveness and feasibility of USG‐PIVA to undertake successful a‐RCEx. Methods: Data was collected prospectively from patients with sickle cell disease and difficult venous access, undergoing a‐RCEx at a single centre. The USG‐PIVA technique was attempted and data relating to each attempt was collected and analysed. Results: Between April 2014 and July 2015 84 USG‐PIVA procedures were performed on 38 patients. 71 USG‐PIVA (85%) were successful, 13 (15%) were unsuccessful. Veins successfully cannulated: in the upper arm, basilic (22), brachial (33) and cephalic (2) veins; in the antecubital fossa, basilic (3) and median cubital (7) and in the lower arm, cephalic (2) and radial (2). Cannulas used: Introcan Safety® Braun 22 g (1), 20 g (9) and 18 g (61). Inlet flow rates achieved: 30–60 ml/min (mean 45 ml/min). Depth of veins cannulated: 2–12 mm (mean 5 mm). two complications were observed—one cannula displacement and one nerve injury. No arterial punctures occurred. Central Venous Catheters avoided (49). Conclusion: The US‐PIVA method offers an effective alternative to Central Venous Access in patients requiring a‐RCEx procedures who lack visual or palpable peripheral access, with minimal complications seen in this series. J. Clin. Apheresis 31:501–506, 2016. © 2015 Wiley Periodicals, Inc.